Gambaran Kepuasan Masyarakat terhadap Kualitas Pelayanan Kesehatan di Wilayah Kerja Puskesmas Jongaya Kota Makassar - Ummu Salamah; Nurhaliza Madani arifin (Yayasan Citra Cendekia Celebes, 2025)
Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 75 of 2014, community health centers (puskesmas) function as the primary healthcare facilities closest to the community, with a primary focus on promotive and preventive efforts. Public satisfaction is an important factor in evaluating the success of healthcare services. This study aimed to describe the level of public satisfaction with the quality of services in the working area of Puskesmas Jongaya. The study was conducted using a descriptive method with a cross-sectional approach. The results showed that of 100 respondents, 69% were female and 31% were male. By age group, the majority of respondents were 26–35 years old (49%), followed by 36–45 years (8%), 46–55 years (21%), 56–65 years (12%), and 66–75 years (10%). Regarding education, 2% of respondents had no schooling, 16% completed elementary school, 16% junior high school, 44% senior high school, 7% diploma, and 15% bachelor’s degree. Satisfaction analysis indicated that 43% of respondents were very satisfied with promotive services, 67% were very satisfied with preventive services, and 54% were very satisfied with curative services. Overall, the highest satisfaction level was recorded among 75% of respondents who expressed being very satisfied with the quality of healthcare services. The study concluded that the majority of respondents were female, aged 56–65 years, had a senior high school education, and worked as housewives. The highest satisfaction was observed in promotive services, and there was a significant relationship between public satisfaction and the quality of promotive services, with a p-value of 0.020 (<0.05).